2019
DOI: 10.1109/tnsre.2019.2911316
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Hybrid Classifier for Myoelectric Pattern Recognition Against the Interferences of Outlier Motion, Muscle Fatigue, and Electrode Doffing

Abstract: Traditional myoelectric prostheses that employ a static pattern recognition model to identify human movement intention from surface electromyography (sEMG) signals hardly adapt to the changes in the sEMG characteristics caused by interferences from daily activities, which hinders the clinical applications of such prostheses. In this paper, we focus on methods to reduce or eliminate the impacts of three types of daily interferences on myoelectric pattern recognition (MPR), i.e., outlier motion, muscle fatigue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…For example, the study reported by [47] proposed a method to classify hand movements through the single-channel sEMG, which did not consider the fatigue situation, and the method can be improved by our strategy. Previous studies have proposed the methods of designing classifiers that are robust against fatigue, such as fuzzy neural networks and adaptive hybrid classifiers [23,24]. However, these methods may be accompanied by increasing the computation and the complexity of classifiers, while our strategy may be easier to use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the study reported by [47] proposed a method to classify hand movements through the single-channel sEMG, which did not consider the fatigue situation, and the method can be improved by our strategy. Previous studies have proposed the methods of designing classifiers that are robust against fatigue, such as fuzzy neural networks and adaptive hybrid classifiers [23,24]. However, these methods may be accompanied by increasing the computation and the complexity of classifiers, while our strategy may be easier to use.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneer studies also focused on improving the classifiers' robustness against muscle fatigue. Song et al [23] and Ding et al [24] have proposed EMG based gesture classifier, which is robust to fatigue by using a fuzzy neural network and an adaptive incremental hybrid classifier-based recognize strategy, respectively. Mainardi et al [25] developed a new double differential electrode that can compensate for the influence of muscle fatigue by modifying its gain.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies involving sEMG for motion intention recognition in the application of rehabilitation robots [79][80][81], and the sEMG signal should be incorporated in the active exercise of the AJC to make the active exercise more real-time and comfortable even though the sEMG signals change due to a variety of factors, such as placement, fatigue and sweat.…”
Section: Multimodal Motion Intention Recognitionmentioning
confidence: 99%
“…In addition to attention, out-of-laboratory myoelectricbased gesture recognition performance is known to be limited by interference including: electrode shift, muscle fatigue, unwanted motion and force variation [34]- [36]. To compensate for this, Ding et al (2019) circumvent the burden of frequent retraining by using an adaptive incremental hybrid classifier [37]. The proposed method retrains target gestures in a semiautomated process by separating classes through resting and active states [37].…”
Section: A Practical Implementationmentioning
confidence: 99%
“…To compensate for this, Ding et al (2019) circumvent the burden of frequent retraining by using an adaptive incremental hybrid classifier [37]. The proposed method retrains target gestures in a semiautomated process by separating classes through resting and active states [37]. While manual input is still required, adaptive classifiers like this and others ( [38]- [40]) may be a promising approach to address real-world EMG variability.…”
Section: A Practical Implementationmentioning
confidence: 99%